Praktik Demograsi Pada Pemilihan Kepala Desa Di Aimas Sorong Provinsi Papua Barat - Lora Ernanta Tarigan; Julia Ivanna (Public Service and Governance Journal, 2024)
The aim of this research is to determine democratic practices in village head elections in Aimas Sorong, West Papua Province. The results of this research show that there are several causes of high community participation in Aimas Sorong, West Papua in the 2022 village elections. There are several main factors for high community participation, namely. There are two theories to find out the factors that cause high community participation, namely political mobilization and then voter behavior. includes a sociological approach, a psychological approach, and a rational choice approach.